Is the black dog really a dalmatian? : an investigation into whether stress impact and attributional style lead to different outcomes for individuals receiving 20 sessions of cognitive behavioural therapy for depression : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Auckland, New Zealand - Good, Kimberly Suzanne (Massey University, 2010)
There is a need for greater clarity in the relationship between psychosocial stress and depression and its application to outcomes in cognitive behavioural therapy (CBT). A preponderance of research focuses primarily on the causal relationship between stress and depression and is limited by the traditional assumption of homogeneity amongst first-episode sufferers of mild to moderate depression. In actual fact, the perceived intensity and type of stress as well as an individual‘s attributional style may create significant differences in how they respond to therapy and overcome depression. This research had four aims: to develop an understanding about why individuals differ in their CBT recovery trajectories; to examine how the stress-diathesis framework relates to treatment outcomes; to develop a way of effectively assessing and measuring the quantitative impact of stress; and to develop an effective approach towards assessing contextual aspects of stress. The research inquiry was guided by stress-diathesis theory and a reformulated stress-diathesis framework was proposed that specified a quantitative – qualitative stress distinction. This accorded with the study‘s development of two stress measures. A measure for objectively quantifying stress was introduced, along with a therapist questionnaire that identifies precipitating stressors in depression and the qualitative aspects of the stress experience. A final sample of 26 clients experiencing their first episode of Major Depressive Disorder (MDD) was achieved. Clients were recruited for 20 sessions of CBT with 2- and 6-month follow-ups. Depression severity was measured each session with the Beck Depression Inventory (BDI-II) and attributional style was measured at six time points with the Attributional Style Questionnaire (ASQ). Stress impact was measured using the Impact of Event Scale – Video Format (IES-VF) and the Identification of Precipitating Stressors Questionnaire (IPSQ) was developed to assess precipitating stressors of depression. Multilevel analysis suggested that attributional style moderates the relationship between change in stress and change in depression. Clients with predominantly depressogenic attributional styles showed a delay in depression improvement compared to clients with non-depressogenic styles, even when significant stress reductions were achieved. Gender, therapy completion and marital status were also significant predictors of recovery. Preliminary support was achieved for the classification of clients into three recovery subgroups, according to whether they achieved rapid, expected or minimal stress improvements. Post-hoc analyses also indicated that chronicity and impact on autonomy appear to be the most influential stressor characteristics. Implications for future research and clinical considerations are discussed.
Keywords: Cognitive Behaviour Therapy; Cognitive therapy; Psychotherapy; Stress; Attributional style; Clinical psychology; CBT; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380107 Health, clinical and counselling psychology